The effect of deemed dividend tax on dividend policy: evidence from Sri Lanka - Samarawickrema, M.D.D.P.; Rathnasingha, D.L.P.M. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
This study aims to find the effect of the Deemed Dividend Tax (DDT) on the dividend payout policy of companies in Sri Lanka. The sample of the study comprises of 100 companies listed on the Colombo Stock Exchange, excluding financial and power and energy sectors, for the period from 2003 to 2014. Further, the study uses the Tobit regression model to analyse the data. The findings of the study suggest that a large number of companies have initiated dividend distribution after the introduction of DDT in 2007 and that dividend payout of companies have increased significantly due to the introduction of DDT. On the other hand, relaxation of DDT threshold in 2011 has prompted companies to decrease the dividend payout, but to a lesser extent compared to the impact of introduction. The findings also discover that dividend income of a company has become a factor that affects dividend policy of a company significantly, after the introduction of DDT. Additionally, the findings show that profitability, stability of earnings, leverage and institutional and corporate ownership affect dividend policy of companies in Sri Lanka significantly. However, it is evident that liquidity position of companies is not considered in dividend policy decisions in Sri Lanka, as the companies are more concerned about reducing their tax liability by avoiding DDT. Moreover, the findings support signalling, catering and tax clientele hypotheses, but refute the tax effect hypothesis. In conclusion, the DDT has affected dividend payout policy of companies and has altered the factors that affect dividend policy in Sri Lanka.
Keywords: Dividend policy; deemed dividend tax; Colombo stock exchange